2022
DOI: 10.1093/infdis/jiac230
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Meningococcal Disease Among People Experiencing Homelessness—United States, 2016–2019

Abstract: Background Recently, several invasive meningococcal disease (IMD) outbreaks caused by Neisseria meningitidis have occurred among people experiencing homelessness (PEH). However, overall IMD risk among PEH is not well described. We compared incidence and characteristics of IMD among PEH and persons not known to be experiencing homelessness (non-PEH) in the United States. Methods We analyzed 2016–2019 IMD data from the National… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Our finding that meningococcal disease incidence among PEH enrolled in Medicaid was 27 times higher than among non-PEH is consistent with a recent analysis of enhanced meningococcal disease surveillance data from the same period, which found that incidence was 19.8 times higher among PEH than non-PEH nationally, or 24.6 times higher among persons aged 18 or more years [5]. Of note, this article also described outbreaks among PEH, including 10 meningococcal disease outbreak cases identified among PEH in Boston, Massachusetts, from 2016 through 2019.…”
Section: Plos Onesupporting
confidence: 92%
See 2 more Smart Citations
“…Our finding that meningococcal disease incidence among PEH enrolled in Medicaid was 27 times higher than among non-PEH is consistent with a recent analysis of enhanced meningococcal disease surveillance data from the same period, which found that incidence was 19.8 times higher among PEH than non-PEH nationally, or 24.6 times higher among persons aged 18 or more years [5]. Of note, this article also described outbreaks among PEH, including 10 meningococcal disease outbreak cases identified among PEH in Boston, Massachusetts, from 2016 through 2019.…”
Section: Plos Onesupporting
confidence: 92%
“…Since our analysis suggests that the presence of certain underlying health conditions may contribute to, but does not fully explain, the increased risk of meningococcal disease among PEH, ensuring PEH have reliable access to the appropriate health care for managing underlying conditions is crucial for the overall health of this population and reduction of infectious disease risk. Additionally, exposure to crowded living conditions has been associated with increased risk of meningococcal disease [2], which is an important consideration for homeless shelters as some meningococcal disease outbreaks have included PEH who visited these facilities [5]. While PEH experience higher rates of vaccine-preventable diseases than the general population, it can be challenging to vaccinate PEH for several reasons, including lack of access to preventative health care, mistrust of providers, and lack of information about infectious disease risk or the importance of vaccination [16][17][18].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Mass gatherings and religious events such as the Hajj and Umrah pilgrimages are also well-recognized risk factors for meningococcal transmission and subsequent outbreaks [ 18 , 19 ]. Risk is also greater in people experiencing homelessness [ 20 ], and in immigrant and refugee populations [ 21 ]. Tobacco smoking and passive exposure may also increase IMD risk [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unstable living conditions have been identified as an extrinsic risk factor for increased exposure to infectious diseases, including meningococcal disease. Homelessness, for instance, is associated with higher meningococcal disease risk due to shelter overcrowding, lower vaccination rates, and increased exposure to other infectious diseases [ 4 , 12 ].…”
Section: Discussionmentioning
confidence: 99%